The Mayflies of New England and Atlantic Canada. - Burian, Steven (Spring;Biology., 1999)
Keywords: dept.bio; faculty_collection; sabbatical_report

Connecticut Birding Guide. - Sabbatical Report - Smith, Dwight R. (1996)
Keywords: dept.bio; faculty_collection; sabbatical_report

Research for Books on the Traditional Japanese Concepts of Nature. - Samuel, Edward (1993)
Keywords: dept.bio; faculty_collection; sabbatical_report

Manual of Ornithology. - Proctor, Noble S. (1990)
Keywords: dept.bio; faculty_collection; sabbatical_report

Manual of Ornithology: Avian Structure & Function - Proctor, Noble S.; Lynch, Patrick J. (Yale University Press, 1993)
Keywords: Anatomy; Birds; Laboratory manuals; dept.bio; faculty_collection

Habitat and spatial relationships of nesting Swainson's Hawks (Buteo swainsoni) and red-tailed hawks (B. jamaicensis) in northern Utah - Bosakowski, T.; Kamsey, R.D.; Smith, D.G. (Great Basin Naturalist, 1996)
A total of 28 Swainson's Hawk (Buteo swainsoni) and 30 Red-tailed Hawk (B. jamaicensis) nests were found in Cache Valley. Utah, during the summers of 1992 and 1993. All nests were in trees, but only Red-tailed Hawks nested in dead trees (30%). In the intensive study area, nesting densities were 0.10 nests/km2 for Swainson's Hawk and 0.08 nests/km2 for Red-tailed Hawk. Nearest-neighbor nest distances were significantly shorter among Swainson's Hawks (1.74 km) than among Red-tailed Hawks (2.83 km). Congeneric nearest- neighbor distances were significantly shorter than conspecific distances for Red-tailed Hawks (1.59 vs. 2.83 km) but not for Swainson's Hawks (1.52 vs. 1.74 km). GIS analysis of habitat types was made for 2-km radii around nest sites. Cropland was the dominant land cover type of nest sites of both species and no significant difference was found between species. Swainson's Hawk nest sites contained significantly more pasture, whereas Red-tailed nest sites contained significantly more juniper, maple, and sagebrush. Only Red- tailed Hawk nests (n=8; 27%) were found on the periphery of the valley at the base of foothills of the Cache Mountains. This preference resulted in a significantly higher elevation for Red-tailed Hawk nest sites. Swainson's Hawk nests occurred only on the valley floor on level terrain. Distance to the nearest paved road and building was very similar for both species, implying that little difference exists in tolerance levels for human activities. Overall, multivariate niche overlap for habitat was high (0.89), indicating a lack of habitat partitioning between these 2 Buteos in Cache Valley.
Keywords: Buteo; Buteo jamaicensis; Buteo swainsoni; GIS; Red-tailed Hawk; Swainson's Hawk; dept.bio; habitat; nest sites; ⛔ No DOI found

Group hunting forays of wintering Northern Harriers, Circus cyaneus: An adaption of juveniles? - Bosakowski, T.; Smith, D.G. (Canadian Field-Naturalist, 1996)
The social interactions of a wintering population of Northern Harriers (Circus cyaneus) were studied in the Hackensack Meadowlands tidal marshes in New Jersey. Juvenile harriers were numerically dominant in the population and participated in hunting groups significantly more often than adult males or females. Group sizes varied from 2-4 birds (total groups observed = 66 duets, five trios and two quartets). The occasional inclusion of adults in a foraging group was usually the result of juveniles following the adult, presumably for the parasitic benefits of grabbing flushed prey or exploiting high yield foraging patches. Our observations suggested a non-territorial wintering harrier population documented by observations of 3-6 different individuals frequently hunting the same 12-ha area each day as well as random use of our study quadrats (3-ha) by individuals of all sexes and ages. Territorial defense was observed in only one adult female, which infrequently attempted to defend a territory. Overall, the prevalence of group-foraging behavior is consistent with the general lack of winter territory in this population.
Keywords: Circus cyaneus; Hackensack Meadowlands; New Jersey; Northern Harrier; dept.bio; following; foraging; group hunting; winter ecology; ⛔ No DOI found

Supermarket botany - Smith, D.G.; Avery, D.F. (American Biology Teacher, 1999)
Keywords: dept.bio

Nest site selection by urban and rural Great Horned Owls in the northeast - Smith, D.G.; Bosakowski, T.; Devine, A. (Journal of Field Ornithology, 1999)
We studied nest site and habitat characteristics associated with 75 Great Horned Owl (Bubo virginianus) nests in Connecticut, northern New Jersey, and southeastern New York. Nest sites were categorized as either urban (30) or rural (45) and were compared to data from available habitat (24 random sites for microhabitat; 70 random sites for macro-habitat). Urban nest trees were significantly larger in diameter and taller than rural nest trees, and accordingly, nests were higher in urban nest trees as well. Urban nest sites were significantly different than random sites for all eight habitat variables, but rural nests were significantly different for only five variables. Urban nests were significantly different than rural nests for five of eight habitat variables. Only urban owl nests had significantly lower site basal area, higher conifer composition, and lower shrub cover. Both urban and rural owl nests showed lower canopy cover and closer proximity to forest edge, paved roads, human habitation, and water than random sites. Although both urban and rural Great Horned Owls demonstrated habitat selection (use different from availability), urban owls showed a stronger degree of selection, probably because of the greater complexity of habitats available in the urban landscape.
Keywords: Bubo virginianus; Coniferophyta; Strigiformes; dept.bio; ⛔ No DOI found

Endoscopy: A Noninvasive Solution - Watson, C.E.; Sobel, D.S. (Veterinary Technician, 1999)
Because clients are demanding better health care for their pets, more advanced and quicker techniques for obtaining a diagnosis are essential. Veterinary endoscopy gives veterinarians and clients a noninvasive option for evaluating diseased tissue without surgical intervention. Although patients must be anesthetized, they often are released from the veterinary facility on the same day the procedure is performed. Technicians play a vital role in communication between veterinarians and clients and provide valuable procedural skills during the endoscopy.
Keywords: dept.bio; ⛔ No DOI found

Centroptilum ozarkensum (Ephemeroptera: Baetidae) a new long-clawed baetid from Missouri - Wiersema, N.A.; Burian, S.K. (Journal of the Kansas Entomological Society, 1999)
Centroptilum ozarkensum, new species is described from distinctive adult males collected from springs within the Ozark National Scenic Rivers area of southeastern Missouri. The adult male of this species is similar to the widespread species C. album, hut is easily distinguished from it by color and morphological characters.
Keywords: dept.bio; ⛔ No DOI found

Response of a forest raptor community to broadcasts of heterospecific and conspecific calls during the breeding season - Bosakowski, T.; Smith, D.G. (Canadian Field-Naturalist, 1998)
We investigated the response of the forest raptor community to broadcasts of all potentially occurring raptors in a New Jersey watershed. Raptors were systematically surveyed using high-volume broadcasts of conspecific and heterospecific calls during the breeding season at a total of 81 survey stations. Results showed 107 responses from 10 species of breeding raptors following 891 broadcasts of 11 species. Among responses that occurred during or after broadcasts, at least 50% of the forest raptor species responded to heterospecific calls. Response rates to conspecific or heterospecific broadcasts were significantly different between hawks (68% heterospecific) and owls (26% heterospecific), suggesting that hawks showed greater heterospecific conflict than members of the owl guild. The hawk guild had a higher species packing (six versus four species) which is thought to increase the likelihood of competition in the community. In addition, most hawks probably need to re-establish territories each spring because the vast majority of them will migrate south for the winter. In contrast, most of the owl guild members are permanent residents and territories may be more permanent. Overall, the prevalence of heterospecific response is an indicator that current competition exists and continues to shape present-day community structure among forest raptors.
Keywords: Behavior; Community; Forest; Hawks; Owls; Raptors; Survey; United States; Vocalizations; breeding season; calling behavior; community structure; dept.bio; forest; intersexual interaction; raptor; ⛔ No DOI found

Toward a professional position on the translocation of problem wildlife - Craven, S.; Barnes, T.; Kania, G. (Wildlife Society Bulletin, 1998)
Keywords: Live capture; Policy; Translocation; Wildlife damage management; dept.bio; ⛔ No DOI found

Distribution and species richness of a forest raptor community in relation to urbanization - Bosakowski, T.; Smith, D.G. (Journal of Raptor Research, 1997)
We studied the species richness and distribution of the forest raptor community in a New Jersey watershed in relation to urbanization. Raptors were systematically surveyed using high volume broadcasts of conspecific and heterospecific calls during the breeding season at a total of 81 survey stations. Ten habitat variables relevant to urbanization were measured at each survey station using topographic maps and aerial photographs. Results showed a community composed of 10 species of breeding raptors. Buteo lineatus, Accipiter gentilis and Strix varia showed a significant avoidance of suburban habitat, whereas B. jamaicensis and Bubo virginianus had a greater tendency to occupy such areas. Lowland habitat was significantly selected by S. varia, B. lineatus and A. cooperii, a habitat usually most susceptible to development in the study region. Raptor species richness showed a strong positive correlation (r = 0.79, P < 0.01) with wilderness area size. No wilderness area less than 1000 ha had more than four raptor species while four to eight species were found in areas from 1000-8000 ha. Utilization of three increasing size classes of wilderness areas showed increasing trends for B. lineatus, A. gentilis and S. varia, and decreasing trends for B. jamaicensis and Bubo virginianus. © 1997 The Raptor Research Foundation, Inc.
Keywords: Community; Forest fragmentation; Forest raptors; Survey; Urbanization; Wilderness; dept.bio; ⛔ No DOI found

First record of Anthopotamus verticis and new records of A. Distinctus (Ephemeroptera: Potamanthidae) in New England - Burian, S.K. (Entomological News, 1997)
The species Anthopotamus verticis is recorded for the first time in New England from the Housatonic River in western Connecticut. Notes on the larval habitat and observations on the sympatric occurrence of this species with A. distinctus are presented. New distribution records for A. distinctus are presented for Massachusetts and Vermont.
Keywords: Anthopotamus distinctus; Anthopotamus verticis; dept.bio; ⛔ No DOI found

New record of Brachycercus maculatus berner (Ephemeroptera: Caenidae) from New York and a key to larvae of northeastern species - Burian, S.K.; Novak, M.A.; Bode, R.W.; Abele, L. (Great Lakes Entomologist, 1997)
Brachycercus maculatus, a member of a rare group of mayflies, is now recorded for the first time from New York State in the upper Hudson River. An illustrated key to the Brachycercus larvae of northeastern North America is provided to spur further study of the genus in the region.
Keywords: Brachycercus maculatus; dept.bio; ⛔ No DOI found

The summer stars program - Cantrell, M.L.; Ebdon, S.A.; Firlik, R.; Johnson, D.; Rearick, D. (Educational Leadership, 1997)
Space, futurism, exploration, and stardom are some of the themes at a summer camp inspired by Howard Gardner's theories.
Keywords: dept.bio; dept.edu; peer-reviewed; ⛔ No DOI found

An introduction to issues of habitat fragmentation relative to transportation corridors with special reference to high-speed rail (HSR) - De Santo, R.S.; Smith, D.G. (Environmental Management, 1993)
Potential environmental impacts on wildlife result from siting and construction (short-term impacts) and habitat removal and fragmentation (long-term impacts) as a consequence of transportation corridor construction. Especially in rural districts, wildlife migration corridors and dispersal orientation are altered or destroyed and wildlife populations and their gene pools are isolated. This significantly weakens the wildlife community. Prudent selection of construction corridors reduces fragmentation impacts by maximizing preserved fragment sizes, and by running parallel to, not through, natural areas. Corridor width determines the degree to which wildlife movement is restricted except that culverts, underpasses, overpasses, and one-way gates, can aid wildlife in cross movements. Minimum underpass dimensions for large wildlife should be no smaller than 14 ft×14 ft and should include natural substratum inverts. Rail corridors have four characteristics that minimize adverse environmental impacts. The railbed is dry, ballast fillters runoff, there is little runoff beyond the toe of slope, and drainage ditches serve to control sheet flow and erosion, sediment movement, and uncontrolled channel flow. Rail corridors usually occupy smaller land areas because they are narrower and are more feasible to elevate so as to allow free movement of wildlife across the corridor. © 1993 Springer-Verlag New York Inc.
Keywords: Environmental impacts; Habitat fragmentation; High-speed rail (HSR); animal; corridor; dept.bio; environmental impact assessment; forest; habitat fragmentation; note; railway; siting; species; united states; wildlife

Niche overlap of two sympatric‐nesting hawks Accipiter spp. in the New Jersey‐New York Highlands - Bosakowski, Thomas; Smith, Dwight G; Speiser, Robert (Ecography, 1992)
The food and habitat niches of two nesting species of hawks Accipiter spp were studied in an extensively forested area of the Eastern Deciduous Forest Biome Nesting habitat was quantitated at 19 Cooper s hawk A cooperu nests and 16 northern goshawk A gentilis nests There was no significant trend for Cooper's hawks to nest in less mature forests than northern goshawks as reported previously for western North America Forest habitats did not differ markedly except that shrub cover was greater at Cooper's hawk nest sites, which were also on flatter terrain and closer to roads, forest openings, and human habitation However, these few differences resulted m reducing habitat‐niche overlap considerably (0 538), as was calculated using principal components analysis Mean prey weight was significantly larger for the northern goshawk which follows its 2 2‐fold body weight advantage over Cooper's hawk Although bird prey was of primary importance to both Accipiter, goshawks took twice the proportion of mammals compared to their smaller congener Food‐niche overlap was lowest by prey species overlap (0 470), followed by prey size class overlap (0 529), and highest by vertical foraging zone overlap (0 816) The Cooper's hawk showed the greatest niche breadth for both food and habitat niches indicating it as more of a generalist Overall, niche complementarity of food and habitat dimensions resulted in niche overdispersion along food and habitat dimensions with a total niche overlap (0 504) that was below the competition threshold These results suggested that competition (past and current) was responsible for segregating niches Copyright © 1992, Wiley Blackwell. All rights reserved
Keywords: Accipiter cooperii; Accipiter gentilis; Cooper's hawk; USA, New Jersey; USA, New York; dept.bio; goshawk; hawk; niche overlap; northern goshawk